HRM Practices Across Different Cultures: An Evidence-Based Study In France And Egypt - Bernandy, Marceli Putri; Wijaya , Anne Ivena; Lestiani, Dwi Indah; Husaini, Ravi; Saputra, Laurensius Herdimas; Oktavian, Fabian Nauval; Rahman, Muhammad Fajar Wahyudi (CV ODIS, 2024)
Human Resource Management (HRM) conceptually encompasses policies, practices and systems that influence employee behaviour, attitudes and performance. The comparative research of HRM between France and Egypt, countries from different continents, Europe and Africa, used the literature study method with a descriptive-qualitative approach. The results showed significant differences in HRM practices between the two countries. France has an intuitive recruitment approach with the use of multiple interview methods, while Egypt tends to use internal and informal recruitment. In development, France focuses on internal relations, while Egypt involves government initiatives. Regarding termination of employment, France has a collective policy (RC), while Egypt is unstable in the tourism sector. Performance appraisal in France is subjective, while in Egypt employees care more about procedural justice. The compensation system in France involves fixed and flexible salaries, while Egypt has government regulations. Occupational Safety and Health (OSH) regulations are stricter in France, reflecting cultural and labour law differences. Thus, cultural and legal differences create different frameworks in France and Egypt, influencing the implementation of HRM in each country.